Frontiers of the Roman Empire (Compilation : 2021) (Oxford)
96 sayfa : resim (renkli), harita (renkli), plan
Keywords: “The Roman military remains of Egypt are remarkable in their variety and state of preservation: forts, quarries whose materials were used in the monumental buildings of Rome, roads which brought the Mediterranean into contact with the Indian Ocean; each reader of this book will enjoy learning more about the remarkable Roman inheritance of Egypt“ --